2020
DOI: 10.1002/leg3.28
|View full text |Cite
|
Sign up to set email alerts
|

Profiling the varietal antioxidative contents and macrochemical composition in Australian faba beans (Vicia faba L.)

Abstract: There is growing interest in pulses such as faba bean for the development of foods with enhanced nutrition, functionality, and health benefits. In this study, seed material from 10 faba bean varieties, grown in replicated field trials in South Australia over consecutive seasons (2016 and 2017), were analysed for ferric reducing antioxidant potential, total phenolics, and total monomeric anthocyanins. Differences in the macrochemical composition of varieties was investigated using attenuated total reflectance m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 23 publications
3
25
1
1
Order By: Relevance
“…The median value for all LcCEs was 64.4 mg GAE/g. Although ORAC and TPC are generally correlated in most matrices (Djordjevic et al 2011;Guleria et al 2013;Johnson et al 2020b), no significant correlation between the TEAC and TPC of the LcCEs was observed here (Pearson r = 0.490; p > 0.05). This is likely due to the small sample size (n=5), given that our primary focus was on anticancer activity.…”
Section: Antioxidant Capacity and Total Phenolic Contentcontrasting
confidence: 69%
“…The median value for all LcCEs was 64.4 mg GAE/g. Although ORAC and TPC are generally correlated in most matrices (Djordjevic et al 2011;Guleria et al 2013;Johnson et al 2020b), no significant correlation between the TEAC and TPC of the LcCEs was observed here (Pearson r = 0.490; p > 0.05). This is likely due to the small sample size (n=5), given that our primary focus was on anticancer activity.…”
Section: Antioxidant Capacity and Total Phenolic Contentcontrasting
confidence: 69%
“…Extractions and subsequent assays were performed in duplicate. Ferric reducing antioxidant potential (FRAP), cupric reducing antioxidant potential (CUPRAC), total polyphenolic content (TPC) and total monomeric anthocyanin content (TMAC) were determined as previously described (Johnson et al, 2020b). The results for FRAP and CUPRAC were expressed in Trolox equivalents (TEs), TPC results in gallic acid equivalents F I G U R E 1 Location of the growing trial at Home Hill (19.8462 S, 147.2448 E).…”
Section: Measurement Of Antioxidant Capacity Phenolics and Anthocyaninsmentioning
confidence: 99%
“…For each variety, triplicate extracts were prepared from the corresponding homogenate. To extract the polar compounds, approximately 5 g of plum homogenate was combined with 45 ml of 90% MeOH (v/v), following the method previously reported by our laboratory (Johnson et al, 2020a(Johnson et al, , 2019(Johnson et al, , 2020b. After vortexing briefly, the tube contents were mixed for 60 mins using an end-over-end shaker (Ratek RM4) operating at 50 rpm.…”
Section: Extraction Of Polar Bioactive Compoundsmentioning
confidence: 99%